O problema de segurança jurídica da decisão arbitral frente aos precedentes judiciais. - Freitas, Fellipe Domingues de Barros (2019)
The instrument of arbitration is an alternative means of resolving disputes, however, because of its mixed nature, the jurisdictional portion, by means of other indications, such as the arbitral award with the force of a judicial enforcement order, made the arbitrator more jurisdictional system than it appears to the initiates in the subject. This binding does not become mandatory from a rule dictated on the subject in question, but it is due to an obligation arising from the arbitration clause or arbitration agreement. The present work has proposed to make this analysis in the doctrine and articles available on the internet on the subject, as well as to construct the idea that there is no hierarchy between the arbitrator and the judge, since the mandate granted by the parties confers this link. The provision is limited as far as the parties have on the arbitration procedure, but once the arbitration of law has been chosen applying national law, then the arbitrator has his creative activity bound to this commandment. Thus, if there is a legal precedent applicable to the case, it should be applied if there is no breach of legal certainty, since in two different procedures, the first one and the second one, two different answers could be given case.